Concepts of Religious Moderation Education at TAPAL KUDA: Linguistic Analysis and Local Wisdom - Muta'allim, Muta'allim; Munir, Misbahul; Pathollah, Akhmad Ghasi; Nawiroh, Luthfiyatun; Muhalli, Muhalli (Proceedings of Annual Conference for Muslim Scholars, 2022)
Indonesia is called a plural country because it consists of various ethnic groups, races, religions, cultures and languages. Thus, the Indonesian people are prone to conflict, especially those related to religious differences. This phenomenon often occurs among teenagers, especially at Tapal Kuda area. The factors that underlie this are the existence of personal interests, the influx of radicalism, economic business, lack of tolerance, increasing politics, fading of local wisdom, excessive sensitivity, miscommunication, and lack of tabayyun attitude. Therefore, this study presents the concept of religious moderation in order to stem this. This study aims to stem the conflict with the concept of religious moderation through a linguistic approach and local wisdom. This research is a qualitative research with observation and interview methods. The data were obtained from interviews with the Tapal Kuda speakers by voice recording and field note-taking. In addition, the researchers also used reflective-introspective methods. The results of this study indicate that (1) The underlying factors are the existence of personal interests, the entry of radicalism, economic business, lack of tolerance, increasing politics, fading of local wisdom, excessive sensitivity, miscommunication, and lack of tabayyun attitude. (2) the concept of religious moderation with a linguistic approach and local wisdom as an alternative solution in stemming conflicts.